Tension Hydrocele. Issue 8 (August 2015) - Dagrosa, Lawrence M.; McMenaman, Kathryn S.; Pais, Vernon M.
<x xml:space="preserve">Abstract</x> Abstract The etiology of acute scrotal pain can vary from a benign process such as mild trauma, appendicular torsion, or epididymo-orchitis to an emergent process such as an incarcerated inguinal hernia, testicular torsion, or rupture. Furthermore, testicular insult often results in a reactive hydrocele that can both cloud the diagnosis and impair the physical examination. Traditionally, the acute scrotum was managed with immediate exploration, but emergency physicians and urologists have increasingly used Doppler ultrasonography to assess vascular flow, aide in the diagnosis, and ultimately guide triage of those patients who require urgent intervention. We describe the case of a 15-year-old boy who presented with 2 days of increasing testicular pain and swelling, confirmed to have a large hydrocele with compromised testicular perfusion, and was managed by emergent operative drainage and repair of a "tension hydrocele" with immediate return of testicular perfusion. To our knowledge, this is the first report of tension hydrocele causing intratesticular vascular compromise in a pediatric patient.